The Implementation of Didikan Subuh Based on an Integrative Thematic Approach to Enhance Character Education - Yahya, Muhamad; Febriani, Suci Ramadhanti; Yelliza, Merri; Amrullah, Muhammad Afif (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
Character education serves as a crucial solution to address the moral degradation among teenagers, prompting the Padang city government to implement the Didikan Subuh program aimed at reinforcing students' character. This research endeavors to analyze the implementation of Didikan Subuh activities, along with the supporting and inhibiting factors. Employing a qualitative research design, the study involved observation of the Didikan Subuh program across four locations, interviews with teachers, and documentation review, including the curriculum of Didikan Subuh. Data analysis was conducted based on Miles and Huberman's theory. The research revealed several key findings: firstly, the implementation of Didikan Subuh in Padang city varies across locations in terms of purpose, activity materials, and evaluation methods. Secondly, supporting factors include an adequate number of certified teachers, a relatively large student population, and sufficient infrastructure availability. However, inhibiting factors such as adverse weather conditions, conflicting events, and lack of discipline among guidance teachers pose challenges. Additionally, there is a shortage of creative and responsible guidance teachers, along with insufficient materials for Didikan Subuh activities. The study underscores that despite its challenges, the implementation of Didikan Subuh has the potential to strengthen character education among students.